Advance in research on barley limit dextrinase - WANG Xu-dong; YANG Juan; ZHANG Guo-ping (浙江大学学报. 农业与生命科学版)
The starch debranching enzyme limit dextrinase (LD, EC 3.2.1.41) is one of the key enzymes in malting, which catalyses the hydrolysis of α-1,6-D-glucosidic bonds in amylopectin and limit dextrin. The methods for purification and activity measurement of the enzyme have been much improved since it was discovered in 1940's. During grain development, the activity of free LD increased initially and then decreased, while the bound LD appeared later, and the increase in its activity is closely associated with the decrease in the activity of free LD. The activity of LD was quite low in mature grains. However, the total activity increased gradually during germination. Recently, the gene encoding barley LD was isolated from a genomic phage library using a barley cDNA clone as probe and the two inhibitors which could form complex with LD in grains also were identified and characterized. It is indicated that the inhibitors have dual impacts on malting process and quality. In this paper the change in LD activity during grain development and germination and its response to environmental factors, genotypic difference and methodology of assaying the activity, and isolation of the genes encoding the enzyme were reviewed.